Studies of the effects of N fertilizers and Microbion UNC biofertilizer on microelement content of horseradish (Armoracia macrocarpa) - Balla Kovács, Andrea (Acta Agraria Debreceniensis, 2010)
A field experiment on calcareous chernozem soil was performed to study the effects of different N and bacterial fertilizers on the nutrient content of horseradish (Armoracia macrocarpa). In the experiment the trials were arranged in a randomized block design with three replications, applying three levels of NH4NO3 and different N fertilizers, namely ammonium-nitrate, urea and calcium-nitrate, with or without application of Microbion UNC biofertilizer. In the present paper the changes and distribution of manganese, zinc and copper contents of the horseradish plant are summarized by the effect of different treatments. The Mn content of leaves were higher in all cases than those of roots, but Zn mainly accumulated in the roots. The distribution of copper within the horseradish plant was more equalized than that of Zn and Mn. Different N fertilizers and increasing doses of ammonium-nitrate had effects mainly on the microelement contents of leaves. The highest Mn contents of plant were measured in treatments of Ca(NO3)2 and Ca(NO3)2+Microbion. The lowest ammonium nitrate dose (N1) decreased the Mn content of leaves compared to control, but further doses (N2, N3) did not alter these values any longer. Microbion UNC biofertilizer did not have any effect on the Mn content of roots, but we measured higher Mn in leaves in some combined treatments. Ca(NO3)2 increased the zinc content in leaves and roots in a noticable manner. With the increasing of NH4NO3 doses, the Zn content of leaves and roots augmented significantly. Neither N fertilizers (or the increasing doses of NH4NO3) nor the biofertilizer application influenced the Cu content of horseradish plant. N fertilizers had higher effects on the microelement content of horseradish, the biofertilizer’s effect was smaller and was not the same in every treatment.